Brecciation at the grain scale within the lithologies of the Winchcombe Mighei-like carbonaceous chondrite - Daly, Luke; Suttle, Martin D.; Lee, Martin R.; Bridges, John; Hicks, Leon; Martin, Pierre-Etienne M. C.; Floyd, Cameron J.; Jenkins, Laura E.; Salge, Tobias; King, Ashley J.; Almeida, Natasha V.; Johnson, Diane (Wiley, 2024)
The Mighei-like carbonaceous (CM) chondrites have been altered to various extents by water–rock reactions on their parent asteroid(s). This aqueous processing has destroyed much of the primary mineralogy of these meteorites, and the degree of alteration is highly heterogeneous at both the macroscale and nanoscale. Many CM meteorites are also heavily brecciated juxtaposing clasts with different alteration histories. Here we present results from the fine-grained team consortium study of the Winchcombe meteorite, a recent CM chondrite fall that is a breccia and contains eight discrete lithologies that span a range of petrologic subtypes (CM2.0–2.6) that are suspended in a cataclastic matrix. Coordinated multitechnique, multiscale analyses of this breccia reveal substantial heterogeneity in the extent of alteration, even in highly aqueously processed lithologies. Some lithologies exhibit the full range and can comprise nearly unaltered coarse-grained primary components that are found directly alongside other coarse-grained components that have experienced complete pseudomorphic replacement by secondary minerals. The preservation of the complete alteration sequence and pseudomorph textures showing tochilinite–cronstedtite intergrowths are replacing carbonates suggest that CMs may be initially more carbonate rich than previously thought. This heterogeneity in aqueous alteration extent is likely due to a combination of microscale variability in permeability and water/rock ratio generating local microenvironments as has been established previously. Nevertheless, some of the disequilibrium mineral assemblages observed, such as hydrous minerals juxtaposed with surviving phases that are typically more fluid susceptible, can only be reconciled by multiple generations of alteration, disruption, and reaccretion of the CM parent body at the grain scale.
Special Issue: The science of the Winchcombe meteorite